Chinese mining investment in Australia and Canada – lessons for Denmark and Greenland - Kristensen, Rasmus Abildgaard (Politica, 2015)
Chinese investment has become a “bogeyman” in the debate on the exploitation of Greenland’s mineral resources, but are there reasons for concern? The article looks at experiences in Australia and Canada, where China has made massive mining investment over the past decade. Both countries have had mostly good experiences with the Chinese investors, although it has been a difficult process marked by popular skepticism and mutual misunderstandings, and where both the Chinese companies and the host country authorities have undergone a steep learning curve. Denmark and Greenland could learn a lot from the Australian and Canadian experiences, which show that the key to success is dialogue and strict regulation. This has forced the Chinese investors to learn and adapt. The article also demonstrates the theoretical value of an institutional perspective, including the concept of organizational learning, in the study of Chinese direct investment abroad.